Erich Neumann – Der mystische Mensch - Véronique Liard (Recherches Germaniques)
At the beginning of his essay, Erich Neumann, a student and friend of C. G. Jung with whom he maintained regular epistolary ties from 1933 until his death in 1960, immediately specified that his subject is not mysticism (die Mystik), but what is of the mystical order (das Mystische). The question he wishes to answer is to what extent this type of mysticism is a general phenomenon common to all, making man a homo mysticus. His purpose will be to establish a mystical anthropology. For Neumann, any experience of the numinous, which finds its source in the creative unconscious, is mystical. Consequently, the problem of the creative unconscious is also the central problem of mysticism. We will first present the different types of mysticism described by Neumann (lower mysticism, hidden mysticism, higher mysticism, ouroboric nihilistic mysticism, transformation mysticism). We will then show the different forms of mysticism distinguished by Neumann according to the period of the individual’s life (first mysticism, high mysticism, end-of-life mysticism). We will rely on C. G. Jung’s theories, which serve as a basis for Neumann’s reflections. We will conclude with three questions that mysticism, as Neumann imagines it, raises: man as an image of God, life after death and salvation.